Pengembangan Aplikasi Penggajian Berbasis Web pada Puskesmas Kimi Nabire untuk Meningkatkan Efisiensi dan Akurasi Pengelolaan Gaji Karyawan - Lely Worisio; Usman Arfan (STMIK Pesat Nabire, 2025)
Managing employee payroll is a crucial aspect in agency administration, including at the Kimi Nabire Community Health Center. The manual payroll system that is still used often causes problems such as calculation errors, late payments and lack of transparency. This research aims to design and develop a website-based payroll application to increase efficiency, accuracy and transparency in payroll management. This application was developed using the waterfall method with PHP and MySQL-based technology, and is designed to be accessed by administration and branch heads. The main features provided include managing employee data, automatic salary calculations, creating digital pay slips, and real-time payroll reports. Test results show that this application is able to reduce calculation errors and speed up the pay slip distribution process. With this application, it is hoped that the Kimi Nabire Community Health Center can manage payroll more efficiently and accurately, as well as becoming a reference for other agencies facing similar problems. This research contributes to the development of a website-based payroll management information system, both academically and practically.